(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
Unethical practices and Professional Misconduct by doctors are on the rise. Due to which trust between doctors and patients have declined and dissatisfaction is on the rise among consumers of healthcare in India. To have disciplinary control over registered medical practitioners in India, Medical Council of India has enacted the Indian Medical Council (Professional Conduct, Etiquettes and Ethics) Regulations, 2002. But due to less emphasis on medical ethics during teaching of medical education in medical colleges, there is no awareness and knowledge among registered medical practitioners. This is one of the reasons for increasing cases against doctors by the patients and/or their attendants. Low legal literacy, complexity of law and statutory provisions (regulations) cases come before various high courts and even before Apex Court of India for enforcement and for interpretation. This paper deals with one such case where a delinquent physician was awarded with penalty of removal of name from State Medical Register/ Indian Medical Register for one year. Doctor challenged the case before Delhi High Court. This Research Paper is an attempt by the author to create awareness among all stakeholders, which help to improve the quality of healthcare in India.